First report of Serotype-1 Marek's disease virus (MDV-1) with oncogenic form in backyard turkeys in Turkey: a molecular analysis study - Ongor, Hasan; Timurkaan, Necati; Abayli, Hasan; Karabulut, Burak; Kalender, Hakan; Tonbak, Sukru; Cetinkaya, Burhan (Bmc, 2022)
Background Marek's disease (MD) is a lymphoproliferative disease caused by Gallid alphaherpesvirus 2 (GaHV-2, MDV-1), which primarily affects chickens. However, the virus is also able to induce tumors and polyneuritis in turkeys, albeit less frequently than in chickens. Results This is the first study in Turkey reporting the molecular characterization of a MDV-1 strain detected in a flock of backyard turkeys exhibiting visceral lymphoma. Here, MEQ, vIL-8, pp38 and 132-bp tandem repeat regions, which are frequently preferred in the pathotyping of MDV-1, were examined. It was determined that the MEQ gene of MDV-1/TR-21/turkey strain obtained in the present study encoded 339 amino acids (1020 nt) and had four proline-rich repeat regions (PPPP). Based on the nucleotide sequence of the MEQ gene of the MDV-1/TR-21/turkey strain, a phylogenetic tree was created using the MEGA-X software with the Maximum Likelihood Method (in 1000 replicates). Our strain was highly identical (> 99.8) to the Italian/Ck/625/16, Polish (Polen5) and some Turkish (Layer-GaHV-2-02-TR-2017, Tr/MDV-1/19) MDV-1 strains. Also, nt and aa sequences of the MEQ gene of our strain were 99.1 and 99.41% identical to another Turkish strain (MDV/Tur/2019) originated from chickens. Sequence analysis of pp38 and vIL-8 genes also supported the above finding. The identity ratios of nucleotide and amino acid sequences of vIL-8 and pp38 genes of MDV-1/TR-21/turkey strain were 99.64-100% and 99.79-100%, respectively, when compared with those of the Polish strain. According to 132-bp tandem repeat PCR results, the MDV-1/TR-21/turkey strain had five copies. Conclusions These results suggested that the MDV-1/TR-21/turkey strain obtained from backyard turkeys can be either very virulent or very virulent plus pathotype, though experimental inoculation is required for precise pathotyping.
Keywords: Turkeys; MDV-1; MEQ; pp38; vIL-8; 132-bp tandem repeats